Suggested in the stars - Tawada, Yōko, 1960- (Tawada, Yōko, 1960- Chikyuu ni chiribamerarete., 2024)
"It's hard to believe there could be a more enjoyable novel than Scattered All Over the Earth-Yoko Tawada's rollicking, touching, cheerfully dystopian novel about friendship and climate change--but its sequel, Suggested in the Stars, delivers exploits even more poignant and shambolic. As Hiruko--whose Land of Sushi has vanished into the sea and who is still searching for someone who speaks her mother tongue--and her new friends travel onward, they begin opening up to one another in new and extraordinary ways. They try to help their friend Susanoo regain his voice, both for his own good and so he can speak with Hiruko. Amid many often hilarious misunderstandings (some linguistic in nature), they empower each other against despair. Coping with carbon footprint worries but looping singly and in pairs, Hiruko and her friends hitchhike, take late-night motorcycle rides, and hop on the train (learning about railway strikes but also packed-train yoga) to convene in Copenhagen. There they find Susanoo in a strange hospital working with a scary speech-loss doctor. In the half-basement of this weird medical center (with strong echoes of Lars von Trier's 1990s TV series The Kingdom), they also find two special kids washing dishes. They discover magic radios, personality swaps, ship tickets delivered by a robot, and other gifts. But friendship--loaning one another the nerve and heart to keep going--sets them all (and the reader) to dreaming of something more. Suggested in the Stars delivers new delights, and Yoko Tawada's famed new trilogy will conclude in 2025 with Archipelago of the Sun, even if nobody will ever want this "strange, exquisite" (The New Yorker) trip to end"--